1982
DOI: 10.1002/ana.410120202
|View full text |Cite
|
Sign up to set email alerts
|

Neurological complications of immunization

Abstract: Vaccines prepared from whole, killed organisms (pertussis and possibly influenza) may cause neurological allergic reactions producing encephalopathy. These reactions are characterized by acute, monophasic demyelinative processes and occur with no greater frequency than 1 per 100,000 vaccine recipients; onset is within 4 days of immunization, and recovery is usually complete. No evidence suggests that these vaccines produce an insidious, progressive encephalopathy. Only with the swine influenza program of 1976 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
3
7

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(61 citation statements)
references
References 92 publications
0
51
3
7
Order By: Relevance
“…As a common feature of vaccination-related neurological disease there is a latency period of 1 ⁄ 2 -3 weeks, however, without specific temporal peaks. Usually, it is preceded by systemic reactions (Fenichel 1982, Shaw et al 1988, Mancini et al 1996, and a type III or IV immune reaction is suggested.…”
Section: Discussionmentioning
confidence: 99%
“…As a common feature of vaccination-related neurological disease there is a latency period of 1 ⁄ 2 -3 weeks, however, without specific temporal peaks. Usually, it is preceded by systemic reactions (Fenichel 1982, Shaw et al 1988, Mancini et al 1996, and a type III or IV immune reaction is suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Todos los pacientes quedaron asintomaticos entre 2 y 5 di'as despues del comienzo de las molestias. Se han descrito si'ntomas similares pero distribuidos en las extremidades inferiores, con una evolution semejante 2 . Blinke y cols.…”
Section: Vacuna De Virus De La Rubeola Vivo Atenuadounclassified
“…Los mecanismos a traves de los cuales las vacunas pueden producir complicaciones no son claros. Se postula que pueden resultar de una respuesta autoiiunune frente al preparado administrado, al organismo inactivado o a ambos, o. por otro lado, ser el resultado de una infeccion directa del sistema nervioso en el caso de las vacunas preparadas con organismos vivos atenuados 2 • 3 , especialmente en receptores inmunodeprimidos 4 . Se han descrito varios sindromes neurologicos asociados con las inmunizaciones, pudiendo ser, algunos, comunes a distintas vacunas 2 .…”
unclassified
See 2 more Smart Citations